Proactive and integrated consultation-liaison psychiatry for older medical inpatients: a mixed methods description of training, care provided and clinician experience in the HOME study - Sharpe, M; Toynbee, M; van Niekerk, M; Solomons, L; Owens, C; Price, A; Yousif, M; Palmer, A; Clay, F; Berk, G; Burns, J; Hill, L; et al. (Elsevier, 2024)
Objectives: To describe the practical experience of delivering a proactive and integrated consultation-liaison (C-L) psychiatry service model (PICLP). PICLP is designed for older medical inpatients and is explicitly biopsychosocial and discharge-focused. In this paper we report: (a) observations on the training of 15 clinicians (seven senior C-L psychiatrists and eight assisting clinicians) to deliver PICLP; (b) the care they provided to 1359 patients; (c) their experiences of working in this new way.